PVP-assisted synthesis of ultrafine transition metal oxides encapsulated in nitrogen-doped carbon nanofibers as robust and flexible anodes for sodium-ion batteries. (15th April 2021) - Zhao, Qingshan; Xia, Zhengzheng; Qian, Tong; Rong, Xianchao; Zhang, Mei; Dong, Yunfa; Chen, Jinqing; Ning, Hui; Li, Zhongtao; Hu, Han; Wu, Mingbo
Abstract: Transition metal oxides (TMOs) with high theoretical capacities are promising anode candidates for sodium ion batteries (SIBs), which yet suffers from inferior cycling stability and rate capability due to large volume change and sluggish transport kinetics during the sodiation/desodiation processes. Herein, a general strategy is developed to fabricate ultrafine TMOs nanoparticles encapsulated in nitrogen-doped carbon nanofibers ( uf -TMOs@N-CNFs, M = Fe, Mn, Zn, etc.) as advanced anodes for SIBs. The uf -TMOs@N-CNFs are facilely synthesized via an in-situ electrospinning and subsequent carbonization strategy, among which polyvinylpyrrolidone (PVP) is employed as an effective dispersant to suppress metal agglomeration and control the size of TMOs. Benefiting from the intimate interaction between ultrafine TMOs and conductive N-CNFs substrates, the uf -TMOs@N-CNFs can efficiently mitigate the aggregation and pulverization of TMOs, facilitate electron/ion transfer, and boost pseudocapacitive charge storage, leading to superior sodium storage performance, including satisfactory reversible capacity, excellent rate capability, and durable cycling stability. Interestingly, the obtained uf -TMOs@N-CNFs membranes also exhibit excellent flexibility to serve as self-supported and flexible electrodes, demonstrating great potential for flexible SIBs. The present work provides a general and feasible method to construct robust and flexible electrodes for energy storage devices. Graphical abstract: Image 1 Highlights: A general strategy is proposed to fabricate ultrafine TMOs encapsulated in N-CNFs. PVP is a crucial dispersant for the synthesis of ultrafine TMOs nanoparticles. The uf -TMOs@N-CNFs composites provide as robust and flexible anodes for SIBs.